UV-activated gas sensor based on ordered mesoporous ZnO–TiO2 heterogeneous composites for trace NO2 detection at room temperature - Guo, Yuan-Yuan; Zheng, Xiao-Hong; Bo, Liang-Bo; Gu, Zi-Qi; Zhang, Cheng; Liu, Yu-Feng (Talanta (Oxford), 2025)
The growing modern industry has promoted the development of gas sensors for environmental monitoring and safety checks. However, the traditional chemical resistance gas sensor still has some disadvantages such as high power consumption and limited detection, mainly due to the lack of charge transfer ability of sensing materials. In this paper, an ordered UV-activated gas sensor with mesoporous ZnO/TiO2 nanotube composite was prepared by precisely controlling the growth of ZnO on the inner wall of TiO2 nanotube. Based on the synergistic effect of Knudsen diffusion, photoactivation, and in situ heterojunction amplification, the charge transfer performance under room temperature of ZnO/TiO2 nanotube composites is improved. Compared to TiO2 nanotube sensor, the ZnO/TiO2 sensor has a 10-fold enhanced response to NO2, and the detection limit is as low as 50 ppb. Moreover, we studied the performance of ZnO/TiO2 sensor on NO2 in campus, street entrance and chemical plant, and comparing with commercial sensor, found that the detection error and detection limit of our sensor is lower, which proves the sensor has great application prospect in practical detection. This work provides a successful method for in-situ construction of ordered mesoporous materials and gives a solution for the design of advanced photoelectric gas sensors. [Display omitted] •Regular and ordered mesoporous ZnO/TiO2 nanotubes were constructed by in-situ growth.•Synergistic effect based on Knudsen diffusion, photoactivation and heterojunction.•Under UV-light, the detection limit is as low as 50 ppb under room temperature.•The ZnO/TiO2 sensor has a 10-fold enhanced response to NO2 than pure TiO2.•Compared with commercial sensors, our sensors have lower detection limits and smaller errors.